Presentations on How to Finance Iran's Higher Education Based on the Global Study Model - Ehsan Ehteshamnejad; Mehdi Pakzad Bonab; Mehdi Ramezani (پژوهش‌های مدیریت عمومی)
AbstractThe use of new financial methods in the higher education sector is one of the main concerns of science and technology researchers due to the ever-increasing limitations of the public budget and the existence of various types of university divisions based on functional changes.Introduction: Many financing methods for universities have been introduced and many studies have been done on them, while many of the traditional financing methods are responsive to the needs of universities today. Identifying and presenting a proposed model for allocating financial credits to universities is a necessity. As a knowledge enterprise, the university follows the activities of production, distribution, transformation and promotion of knowledge. A desirable model for financing the financial activities of public universities is a model that firstly includes all the mentioned activities, secondly, it creates three efficiency, quality and justice in universities, and thirdly, it develops universities for development. Raise their own quality and quantity. (Entezari, 2018:17). Financing universities is one of the important challenges of the higher education system. The dual financing makes university managers to simultaneously implement reports on maintaining and improving the academic level of the university, along with increasing the amount of wealth creation. This importance can be easily seen by delving into the financing methods of the world's top universities that have achieved such success (Ahmadi & Norozi, 2015:47). Financing and management of important financial resources is the factor of survival of universities and higher education institutions. The consequences of this recession in academic fields will be heavy in a way that will change attention in national and transnational dimensions (Keshavarzade & Ghasemi, 2017:94). The main purpose of this research is to provide financial services for higher education in Iran through the examination of experiences What are the methods (framework, model or students) of selected global higher education financial services? What is the proper financing of the country's higher education inspired by global trade? Does the diversity of disciplines require different methods and financial disciplines or not? What are the policy suggestions for successful implementation determined for Iran's conditions? Among the questions that are searched according to the results of this research, they are answered.Materials and Methods  In this research, both the documentary research method (books, articles, authoritative magazines, etc.) in English and Farsi, and a researcher-made questionnaire were used to implement the KAP model. In the comparative study, an initial model for the financing of higher education in Iran is presented, and then to auxiliary tools and using the theme analysis method, and processing related to semi-structured questionnaires in NVIVO software, the optimal range. A proposal for financial services for higher education in Iran is presented. The target population of this research is 30 people of the higher education complex in Iran, which was randomly selected from among the experts, managers and expert experts who have the opinion and possess this collection. This research was conducted in Iran (spatial domain), between December 2021 and June 2022 (temporal domain) with the participation of higher education financing (thematic domain). Discussion and Results: The results of the surveys showed that despite the difference in the common methods of providing financial resources in public and private universities, the common methods of providing financial resources in the country's universities include political combing, payment based on the quality of the student's quality based on or based on predetermined specific programs and functions, while in other countries they use the general methods of government support, tuition fees, donors and other sources. Although each of these general methods have more detailed components for others. ConclusionUsing the methods of changing the structure of higher education and reviewing the way of allocating basic budgets, special budgets for specific priorities and policies in higher education, allocating incentive budgets, benevolent recruitments through giving incentives. Taxes for benefactors as well as social contracts between the government and the people can improve and upgrade the financial resources of universities. Now that it is possible to make this path smoother with the lens of tax exemptions for revenue-generating contracts of universities.